Tolerance to high temperature in F-5 inbred lines of tomato - Santos, Lucas S. [UNESP] (2014)
High temperatures in the growing tomato have caused a reduction in fruit set and consequently productivity. This work aimed to evaluate F-5 lines of tomato to fruit set and high temperature tolerance in two culture environments. Two experiments were carried out, one in cultivation in greenhouse and the other in the field conditions, from February to June 2012. We evaluated 20 lines F-5 of tomato, originating from the segregation of hybrid SE 1055 F-1, developed for the hot and humid conditions, with resistance to Fusarium oxysporum f.sp. lycopersici race 2, the tomato mosaic virus (ToMV), the Verticilium dahliae and geminivirus (TYLCV) and the control cultivar Yoshimatsu and own hybrid SE 1055 F1. The experiment was performed in a randomized blocks design with 22 treatments, four replications and plots with two plants. We evaluated the total number of fruits per plant (NTF/PL), mass of unmarketable fruits per plant (MFNC/PL), fruit set (PEG), mass of marketable fruits per plant (MFC/PL) and yield of marketable fruits (REND). In the greenhouse were recorded higher temperatures and lower luminosity than in field cultivation. Lines 08, 12 and 13 showed higher fruit set in a greenhouse, being more suitable for cultivation at high temperatures. In the field, the lines 06 and 08 showed that marketable fruit production did not differ from 'Yoshimatsu'. Comparing the field experiment average with the average of greenhouse, a higher fruit set and a higher mass of marketable fruits per plant was achieved in field.